THE INFLUENCE OF COLONIALISM ON THE DEVELOPMENT OF RELIGIOUS LIFE IN TIMOR LESTE - Salampessy, Abdul Kadirsyam; Pulungsari Hadi, Rahadjeng (UI Scholars Hub, 2025)
Timor-Leste is the youngest country in the world with unique religious dynamics. The Catholic population increased rapidly after independence, while the Muslim population decreased drastically due to political dynamics. The presence of Mari Alkatiri, an Arab-descended Timorese Muslim who became Prime Minister (PM) twice, is a depiction of the presence of Islam in a Catholic-majority country. The long history of colonialism in Timor-Leste has greatly influenced the landscape of religious life there. In its development, the people of Timor-Leste live harmoniously and democratically. This journal uses a qualitative research method that focuses on the social and cultural phenomena of the religious life of the people of Timor-Leste. The approach is historical and narrative about the history of the entry of religion, the role of political and religious figures, and changes in the demographics of the population that are influenced by the domestic political landscape. The method used is a literature study with historical documentation. The theory used by the author is the Multiculturalism Theory by Bikhu Parekh, because it discusses the existence of an Islamic minority in the midst of a Catholic majority. Also, how a Muslim figure can have a big role in the political arena of this Catholic-majority country. From this study, several conclusions were found, including that the Muslim population decreased drastically after East Timor's independence from Indonesia due to the development of the political situation there. Islam, which is now a minority, was actually the first religion to enter there, brought by the Hadramaut Arabs. Catholicism then spread massively through Portuguese colonialism.